OTONG, TIMUN, TERONG, ATAU BURUNG: MENELISIK MITOS SISTEM PENANDAAN ORGAN SEKSUAL PRIA - Ronald Maraden Parlindungan Silalahi (Universitas Bunda Mulia, 2016)
Otong (proper name for boy in Sundanese culture)’, timun (cucumber), terong (eggplant), burung(bird) are some examples of naming system for male genitals. This phenomenon bring us to a question why many termsare used referring to Male Sexual Orga ‘genitals’. Globally, Male Sexual Organs can be seen (defined) in various waysbasedon the perspectives used.This article itself viewsMale Sexual Organs from the perspectiveof semiotics.This article is descriptively directed to comprehensively analyze the myth behind the signification system of male sexual organs naming. Refering to the core ideasof semiotics developed by Roland Barthes ( 1957 ), this study is specifically devoted to find the lexical configuration (metalanguage) used to represent male sexual organ and find the connotationsconstructed behind the lexical configuration used to mark the sexual organs.This article is based on a qualitative research by using semiotic approaches. In order to achieve the designated targets, the writer (1) collect metalanguages refering to male sexual organs from some electronic articles, (2) identify and find linguistic environment where the metalanguages are used, (3) analyze contextually the used of metalanguages, (4) classify and determine the signification pattern used. In the research, the writer find 23 metalanguages (expressions) refering to Male sexual organs. From 23 expressions found, the writer classifies the metalanguage into seven types. This classification is the basis used in identifying the connotation of metalanguages.Keywords : Male sexual organs, Myth, Conotation, and Metalanguage